Hidden Translators : the Invisibility of Translators and the Influence of Lawyer-Linguists on the Case Law of the Court of Justice of the European Union - McAuliffe, Karen (Language and Law / Linguagem e Direito, 2016)
<span style="font-family: verdana, Arial, Helvetica, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">Since the mid-1990s, when Lawrence Venuti published his book The Translator’s Invisibility, there has existed, in the eld of literary translation, a debate on the (in)visibility, power and inuence of translators on literature and academic theory. This paper shifts that debate to the eld of legal translation, focusing on the role of and work done by lawyer-linguists at the Court of Justice of the European Union (ECJ) in terms of their (in)visibility in the process of text production of that court and in the texts themselves. Data presented here demonstrate that, in the ECJ itself, as in other elds, translation tends to be “a largely misunderstood. . . practice” (Venuti, 2008: vii), but that recent shifts in dynamics within that institution are leading to changes in perceptions of translation and more ‘visibility’ for translators in the process of production of that court’s case law, although they remain largely invisible in the context of the texts themselves. However, the invisibility of translators in this context necessarily leads to a certain amount of power and inuence on the texts they produce. Since those texts, in particular judgments of the ECJ, are intended to have force of law and to be applied uniformly throughout the 28 EU member states, that power and inuence is not insignicant. This paper analyses some examples of such ‘inuence’ on ECJ case law, and thus on EU law more generally. If we are to develop a full and nuanced understanding of the case law of the ECJ, the power of translators should not be ignored.